PENGARUH INTERVENSI EDUKASI TERHADAP KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE - Riana Angriani; Fitriani Bancin (Universitas Methodist Indonesia, 2023)
Anemia in pregnant women is still a public health problem in Indonesia. One effort to prevent anemia is by administering Fe tablets. However, compliance of pregnant women in consuming Fe tablets is still low. It is hoped that educational intervention can increase the compliance of pregnant women in consuming Fe tablets. This research aims to determine the effect of educational intervention on the compliance of pregnant women in consuming Fe tablets. This research design is quasi-experimental with a pre-test and post-test design. The sample for this study was 60 pregnant women who were divided into two groups, namely the intervention group (30 people) and the control group (30 people). The intervention group was given education about the benefits of Fe tablets, the correct way to consume them, and side effects. The control group was not given education. Data were analyzed using the t-test. The results showed that there was a significant difference between the intervention group and the control group in terms of adherence to consuming Fe tablets (p-value = 0.001). In the intervention group, the proportion of pregnant women who adhered to taking Fe tablets increased from 20% to 80% after the educational intervention. In the control group, the proportion of pregnant women who adhered to taking Fe tablets did not change (from 20% to 20%). In conclusion, educational interventions can increase the compliance of pregnant women in consuming Fe tablets.